Assessment of species composition, diversity and carbon sequestration potential of mangrove forests along the coastline of Borongan City, Philippines - Tabunda, Jared Lorenzo Q.; Malanguis, Jessa May (Tacloban City Division of Natural Sciences and Mathematics, University of the Philippines Tacloban College, 2023)
This study assessed the species composition, diversity, and carbon sequestration potential of the mangrove forests in Borongan City, Eastern Samar, Philippines. A quadrat sampling technique and a stratified random sampling approach were conducted to facilitate the inventory and measurement of trees. Shannon-Wiener Index, Importance values, and allometric equations were used to determine the species diversity, relative importance values per each species, and biomass and tree carbon storage, respectively. For the natural stands, 15 mangrove species belonging to 7 families were identified, with Sonneratia alba and Avicennia marina as the dominant species. On the other hand, 8 mangrove species were observed in the planted stands belonging to 5 families, with Rhizophora apiculata and Avicennia marina being the most dominant species within the stand type. The community species diversity for both the natural and planted stands was low (H2.0261 and H 1.7592, respectively). Among the determined stand types, the mean C-stock value was higher in the natural stands (302 Mg C ha'') than in the planted stands (86.89 Mg C ha). The mangrove forests in Borongan City have the potential to sequester and store as high as 194 Mg Cha which is equivalent to 715 Mg CO, ha. The regression models also indicate that there is a strong association between select dendrometric parameters (Basal area, DBH) with the C-stock value. Hence, this study concludes that despite the lean species diversity in Borongan City, its mangrove stands have the potential to sequester and store huge quantities of atmospheric carbon.
Undergraduate thesis (B.S. in Biology) -- University of the Philippines, Tacloban.